Disturbance and Wetland Type Alter Reed Canarygrass Cover in Northern Michigan. (March 2014) - Marlor, Kathryn M.; Webster, Christopher R.; Chimner, Rodney A.
Abstract: Although much is known about the physiological capabilities of reed canarygrass (RCG) and the consequences of invasion, less is known about the roles that wetland type and surrounding disturbances play in facilitating the spread of RCG in predominantly forested landscapes. Therefore, the goals of our study were to test if (1) certain wetland types in the Northern Great Lakes region were more susceptible to RCG invasion, (2) certain disturbances facilitated RCG, and (3) the level of road development and the presence or absence of a ditch bordering each observed road influences the frequency of adjacent RCG populations. We randomly selected 28 wetlands within the Keweenaw Bay Indian Community reservation in the Upper Peninsula of Michigan. At each wetland, we collected plant community and environmental data and catalogued disturbances. In all, 287 plant species were identified. Cluster analysis revealed 16 distinct vegetation communities, which were distributed among three broader wetland community types: (1) nonforested graminoid, (2) Sphagnum peatlands, and (3) forested wetlands. Occurrence of RCG was most common in the nonforested graminoid communities and was also positively correlated to disturbance. The most frequent disturbances were roads, off-road vehicle trails, and logging activity. Additionally, paved and graded roads, and roads with ditches, were more likely to have RCG alongside them than unpaved dirt roads. Our data suggest that RCG occurrence is controlled by interactions between wetland types and disturbance.